(untitled) (World Bulletin of Management and Law, 2025)
Global economies and governance structures are changing as a result of artificial intelligence (AI), which presents both revolutionary opportunities and serious threats to ethical standards, public trust, and data privacy. Uzbekistan ranks 70th in the AI Readiness Index and faces challenges in AI governance due to underdeveloped legal frameworks and lack of ethical standards. This article analyzes Uzbekistan’s current AI regulatory environment, data privacy issues, and ethical considerations in light of global practices, proposing recommendations aligned with international standards and local needs